Seaweed Aquaculture for Food Security, Income Generation and Environmental Health in Tropical Developing Countries - World Bank Group (World Bank, Washington, DC, 2016)
To meet carbon emissions targets, more than 30 countries have committed to boosting production of renewable resources from biological materials andconvert them into products such as food, animal feedand bioenergy. In a post-fossil-fuel world, an increasingproportion of chemicals, plastics, textiles, fuels and electricity will have to come from biomass, which takesup land. To maintain current consumption trends theworld will also need to produce 50–70 percent more foodby 2050, increasingly under drought conditions and onpoor soils. Depending on bioenergy policies, biomassuse is expected to continue to rise to 2030 and importsto Europe are expected to triple by 2020. Europe isforecast to import 80 million tons of solid biomass peryear by 2020. The expansion of seaweed farming in tropical developingcountries could have large positive impacts on localpoverty, ecosystem management and climate changemitigation. Being able to produce enough biomass and protein for the growing and increasingly wealthyhuman population with no new land and freshwater expropriation for agriculture would dramatically reducehumanity’s ecological footprint relative to currenttrends and projections. The growth of seaweed farming is constrained primarily by lack of proper marine spatial plans and appropriate financing. The current industry in the tropics isbased on inshore areas where multiple conflict ingusers vie for space.The need for technological improvements has consequentimplications for scale of investment, which couldbe a hindrance to many potential seaweed growers,creating space for government engagement to supportnew smaller and medium-scale entrepreneurs.Other opportunities for engagement by governmentsand international agencies committed to sustainable development include investments in transport infrastructure,storage facilities, food preparation and/or hydrocolloid extraction plants, applied researchin solar drying and biogas technology inter alia,technical training and marine spatial planning.